The relationship between communication skills and organizational culture and employe work effectiveness: a case study of UPT Balai Yasa Pulubrayan PT. Kereta Api Indonesia (Persero) - Julienda Br Harahap; Tika Indria (International Enterprise Integration Association, 2026)
This study aims to analyze the influence of communication skills and organizational culture on employee work effectiveness at UPT Balai Yasa Pulubrayan PT. Kereta Api Indonesia. This study uses a quantitative approach with a correlational design. The population and sample amounted to 91 employees determined through a total sampling technique (census). Data were collected using a questionnaire with a Likert scale of 1–5 that has met the validity and reliability requirements with a Cronbach's Alpha value between 0.810 and 0.875. Data analysis was carried out using a Multiple Linear Regression model using IBM SPSS software version 25, which has passed the classical assumption test including the normality test. The research findings indicate that partially, communication skills and organizational culture have a positive and significant effect on work effectiveness. Simultaneously, both variables have a significant effect on employee work effectiveness. This regression model has a coefficient of determination (R-Square) value of 38.9%, which indicates the model's ability to explain variations in work effectiveness, while the remaining 61.1% is influenced by factors outside this study. This study confirms that strengthening organizational culture and improving interpersonal communication skills are key drivers of work effectiveness in the railway industry. Practically, the management of UPT Balai Yasa is advised to intensify communication training programs and internalize work culture values ​​to minimize operational errors and improve service quality.